On Approximating Strongly Dispersion-Managed Solitons (Communications in Computational Physics, 2018)
We use a generalized scaling invariance of the dispersion-managed nonlinearSchrödinger equation to derive an approximate function for strongly dispersion-managedsolitons. We then analyze the regime in which the approximation is valid.Finally, we present a method for extracting the underlying soliton part from a noisypulse, using the resulting approximate formula.